Pengaruh Cara Pengeringan terhadap Perolehan Kadar Senyawa Fenolat dan Aktivitas Antioksidan pada Tumbuhan Meniran (Phyllanthus niruri, Linn.) - Harrizul Rivai; Nining Hijrahwati; Mahyuddin Mahyuddin (STIFARM Padang, 2009)
The effect of drying methods on gaining of phenolic content and antioxidant activity of Phyllanthus niruri herbs have been investigated. The phenolic content was determined by using Folin-Ciocalteu method and antioxidant activity was determined by DPPH method. Result of this investigation showed that phenolic content of fresh, air drying, 400C oven drying, and 600C oven drying were 4.965 mg/g; 0.972 mg/g; 2.022 mg/g and 1.625 mg/g, respectively. IC50 of these sample were 0.445 mg/mL; 4.030 mg/mL; 0.697 mg/mL and 1.875 mg/mL.